1996
DOI: 10.1099/00207713-46-2-588
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lactobacilli by Southern-Type Hybridization with a Lactobacillus plantarum pyrDFE Probe

Abstract: Lactobacillus plantarum, Lactobacillus pentosus, and Lactobacillus paraplantarum (M.-C. Curk, J.-C. Hubert, and F. Bringel, Int. J. Syst. Bacteriol. 46595498, 1996) can hardly be distinguished on the basis of their phenotypes. Unlike L. plantarum and L. paraplantarum, L. pentosus ferments glycerol and xylose but not melezitose. We identified two L. pentosus strains (CNRZ 1538 and CNRZ 1544) which ferment glycerol and melezitose but not xylose. a-Methyla-mannoside was fermented by 66% of the L. plantarum strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
47
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 19 publications
1
47
0
Order By: Relevance
“…Of the food isolates, 20 belonged to L. plantarum, 2 belonged to L. pentosus, and 3 remained unidentified (Table 1). However, a recent taxonomic study (4) claimed that the phenotypic differentiation of L. plantarum and L. pentosus is difficult. Furthermore, L. paraplantarum, a species phenotypically indistinguishable but taxonomically distinct from the above two species has been proposed by other investigators (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the food isolates, 20 belonged to L. plantarum, 2 belonged to L. pentosus, and 3 remained unidentified (Table 1). However, a recent taxonomic study (4) claimed that the phenotypic differentiation of L. plantarum and L. pentosus is difficult. Furthermore, L. paraplantarum, a species phenotypically indistinguishable but taxonomically distinct from the above two species has been proposed by other investigators (6).…”
mentioning
confidence: 99%
“…The present study indicated that tannase activity is common in L. plantarum, L. paraplantarum, and L. pentosus. This enzymatic property may have an ecological advantage for these Lactobacillus species, as they are often associated with fermentation of plant materials (4). For example, the observed occurrence …”
mentioning
confidence: 99%
“…Under these conditions, the synthesis of bacteriocins has a unique role in the ecology of lactic acid bacteria and represents an efficient tool to control the spoilage and poisoning of raw vegetables and fruits (21). Lactobacillus plantarum is a highly heterogeneous and versatile species (22) that is widely found in fermented vegetables and fruits (23). Most of its regulatory systems are strictly related to detection of specific environmental signals (24), competition with other bacteria, and survival under a variety of conditions.…”
mentioning
confidence: 99%
“…The taxonomic positions of these organisms have remained uncertain. When we studied the restriction fragment length polymorphisms of the de novo biosynthetic pyrimidine genes (2), four strains previously identified as L. plantarum strains (strains CNRZ 188ST [T = type strain], CNRZ 1887, 61D, and ATCC 10776) produced peculiar restriction profiles. The L. plantanim strains produced three bands (at 7, 4, and 1 kb), whereas the L. pentosus strains produced only one band (at about 7 kb) and strains CNRZ 1885T, CNRZ 1887, 61D, and ATCC 10776 produced two bands (at 4 and 1 kb).…”
mentioning
confidence: 99%